Models of the three-dimensional structures of echidna, horse, and pigeon lysozymes: calcium-binding lysozymes and their relationship with alpha-lactalbumins. - Acharya, K; Stuart, D; Phillips, D; McKenzie, H; Teahan, C (Kluwer Academic Publishers-Plenum Publishers, 1994)
Similarities in amino acid sequences, three-dimensional structures, and the exon-intron patterns of their genes have indicated that c-type lysozymes and alpha-lactalbumins are homologous proteins, i.e., descended by divergent evolution from a common ancestor. Like the alpha-lactalbumins, echidna milk, horse milk, and pigeon eggwhite lysozymes all bind Ca(II). Models of their three-dimensional structures, based on their amino acid sequences and the known crystal structures of domestic hen eggwhite and human lysozymes and baboon and human alpha-lactalbumins, have been built. The several structures have been compared and their relationships discussed.